Asymmetric radiation transfer based on linear light-matter interaction. (November 2017) - Jia, Zi-xun; Shuai, Yong; Zhang, Jia-hui; Tan, He-ping
Highlights: Asymmetric radiation transfer in a linear metamaterial with its physical meaning has been numerically demonstrated via Finite-Difference Time-Domain method and Rigorous Coupled Wave Analysis. The physical picture of the asymmetric light-matter interaction has been investigated. Dispersion relationship of surface plasmon polariton and temporal coupled mode theory have been employed to verify the results. Abstract: In this paper, asymmetric radiation transfer based on linear light-matter interaction has been proposed. Two naturally different numerical methods, finite difference time domain (FDTD) and rigorous coupled wave analysis (RCWA), are utilized to verify that asymmetric radiation transfer can exist for linear plasmonic meta-material. The overall asymmetry has been introduced to evaluate bifacial transmission. Physics for the asymmetric optical responses have been understood via electromagnetic field distributions. Dispersion relation for surface plasmon polariton (SPP) and temporal coupled mode theory (TCMT) have been employed to verify the physics discussed in the paper. Geometric effects and the disappearing of asymmetric transmission have also been investigated. The results gained herein broaden the cognition of linear optical system, facilitate the design of novel energy harvesting device.